2022
DOI: 10.1101/2022.04.06.22273516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 epidemic on mortality in rural coastal Kenya

Abstract: Background: The impact of COVID-19 on all-cause mortality in sub-Saharan Africa remains unknown. Methods: We monitored mortality among 306,000 residents of Kilifi Health and Demographic Surveillance System, Kenya, through four COVID-19 waves from April 2020-September 2021. We calculated expected deaths using negative binomial regression fitted to baseline mortality data (2010-2019) and calculated excess mortality as observed-minus-expected deaths. We excluded deaths in infancy because of under-ascertainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The population-incidence of hospital-attended paediatric snakebite has been consistently high despite substantial population growth, thus resulting in a growing burden of disease. There was a substantial fall in hospital-attended snakebite incidence in 2021, which is likely to be due to the SARS-CoV-2 pandemic dissuading people from attending hospital [16]. The population-incidence of hospital-attended paediatric snakebite rises with increasing age, and peaks at 8-11 years.…”
Section: Discussionmentioning
confidence: 99%
“…The population-incidence of hospital-attended paediatric snakebite has been consistently high despite substantial population growth, thus resulting in a growing burden of disease. There was a substantial fall in hospital-attended snakebite incidence in 2021, which is likely to be due to the SARS-CoV-2 pandemic dissuading people from attending hospital [16]. The population-incidence of hospital-attended paediatric snakebite rises with increasing age, and peaks at 8-11 years.…”
Section: Discussionmentioning
confidence: 99%
“…The case with anaphylactic hypotension subsequently died due to this complication (Table 3). Amongst children receiving antivenom, 7 (5.9%) received subcutaneous adrenaline (as treatment, rather than prophylaxis), 19 The mean duration of hospital stay was 6.3 days (SD 17.8 days). There was an average of 195 bed-days occupied per year due to paediatric snakebite admissions.…”
Section: Hospital Managementmentioning
confidence: 99%
“…There was a substantial fall in hospital-attended snakebite incidence in 2021, which may have been caused by the SARS-CoV-2 pandemic altering health seeking behaviour [19]. One quarter of paediatric snakebite cases were given antivenom, which was most frequently indicated for local envenoming.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…There are limited studies that have used verbal autopsy data to conduct a comparison of deaths attributable to specific causes pre-and-during the COVID-19 period. A study conducted in rural coastal Kenya reported a transient reduction in deaths attributable to acute respiratory infections in 2020 [32]. A few other modelling studies, though not utilizing verbal autopsy data, have predicted significant increases in deaths due to other communicable diseases such as malaria, tuberculosis and HIV/AIDS due to the effects of the COVID-19 pandemic in sub-Saharan Africa [33][34][35].…”
Section: Plos Global Public Healthmentioning
confidence: 99%